Faktor yang Berhubungan dengan Kejadian Diare pada Balita di Wilayah Indonesia Tengah (IFLS 2014) - Fety Fathimah Al Mubarokah; Ratu Ayu Dewi Sartika (LPPM Hang Tuah Pekanbaru, 2022)
Diarrhea is the second leading cause of death in children under five in the world. Every year at least 1.7 million cases of diarrhea in children occur. This study was conducted to determine the factors associated with the incidence of diarrhea in toddlers in the Central Indonesia region. This study uses data from IFLS 5 in 2014. The sample of this study was toddlers aged 6-59 months in the provinces of Bali, West Nusa Tenggara, South Kalimantan, and South Sulawesi. The research design used was cross-sectional with a sample size of 1079 toddlers. It is known that 16.8% of children under five in Central Indonesia experience diarrhea, with the largest percentage being 17.75% in West Nusa Tenggara. Based on the results of the multivariate test, it was found that age (p-value: <0.001), gender (p-value: <0.003), and household waste management (p-value: <0.017) were associated with diarrhea. Age is the dominant factor in the incidence of diarrhea in toddlers in Central Indonesia (OR: 2.421, 95% CI = 1.739-3.370), meaning that children aged 6-23 months have a 2.4 times risk of suffering from diarrhea. This is due to the reduced immunity of the child obtained from the mother, increased growth and development of the child, and the start of weaning at that age. Strengthening understanding and commitment to implementing PIS-PK is needed to provide health information related to the prevention and treatment of diarrhea conveyed by an approach to families of children under five, thereby raising health awareness starting from the family.